Efficacy of erector spine plane block in two different approaches to lumbar spinal fusion surgery: a retrospective pilot study - Birnbaums, Jānis Verners; Ozoliņa, Agnese; Solovjovs, Leonids; Glāzniece-Kagane, Zane; Nemme, Jānis; Logina, Ināra (Frontiers in Medicine, 2024)
Background Erector spine plane block (ESPB) has been widely used in spinal surgery, although there are variable data about its efficacy. Objectives This study aimed to evaluate the efficacy of ESPB in elective lumbar spinal fusion surgery patients with two different surgical approaches. Materials and methods Retrospectively, 45 elective lumbar transpedicular fusion (TPF) surgery patients undergoing open surgery with different approaches [posterior transforaminal fusion approach (TLIF) or combined posterior and anterior approach (TLIF+ALIF)] were divided into 2 groups: general anesthesia (GA, n = 24) and general anesthesia combined with ESPB (GA + ESPB, n = 21). The primary outcome was to analyze the efficacy of ESPB in two different surgical approaches in terms of pain intensity in the first 48 h. Secondary: Fentanyl-free patients and opioid consumption in the first 24 h postoperatively. Comparative analysis was performed (SPSS® v. 28.0) (p < 0.05). Results Out of 45 patients (27 female), 21 received GA + ESPB and 24 received GA. The average age was 60.3 ± 14.3 years. Chronic back pain before the operation was registered in 56% of patients. ESPB was performed in 17 TLIF and in 4 TLIF+ALIF patients. ESPB significantly reduced pain intensity at rest in both surgical approaches 48 h after surgery (p < 0.05). The need for postoperative fentanyl infusion was significantly lower in the group treated with GA + ESPB in both surgical approaches than in those who only received GA (29% vs. 77% in TLIF and 0% vs. 80% in TLIF+ALIF); p = 0.01 and p = 0.004. Additionally, we observed that ESPB provides a good analgesic effect for up to 6.8 ± 3.2 h in the TLIF and 8.9 ± 7.6 h in the TLIF+ALIF approaches. Consequently, ESPB reduced the initiation of the fentanyl compared to GA alone, with a mean difference of 3.2 ± 4.2 h in the TLIF subgroup (p = 0.045) and 6.7 ± 5.3 h in TLIF +ALIF (p = 0.028). Only in the TLIF+ALIF approach, ESPB reduced the total fentanyl consumption compared to those with GA (1.43 ± 0.45 mg/24 h vs. 0.93 ± 0.68 mg/24 h; p = 0.015). Conclusion ESPB significantly reduced pain at rest after surgery, the number of patients requiring immediate postoperative fentanyl analgesia, and total fentanyl consumption in both surgical approaches, particularly in TLIF+ALIF. However, the application of ESPB does not always provide completely sufficient analgesia.